Pengaruh Budaya Organisasi, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai pada Dinas Kesehatan Provinsi Maluku - Jane Marlevi Pakaila; Ferdy Leuhery (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of organizational culture, work motivation and work discipline on employee performance. There are 3 hypotheses tested namely (1) There is a positive and significant influence between organizational culture on Employee performance, (2) There is a positive and significant influence between work motivation and Employee performance, (3) There is a positive and significant influence between work discipline on Employee performance. The sample used in this study was 54 employees of the Maluku Provincial Health Office. The sampling technique uses purposive random sampling. Data collection techniques used were questionnaires and documentation studies. The analytical test tool used in this study is by using multiple linear regression analysis with classical assumptions. The results of this study are (1) Organizational culture has a significant positive effect on the performance of employees of the Maluku Provincial Health Office, (2) Work motivation has a significant positive effect on the performance of employees of the Maluku Provincial Health Office, (3) Work discipline has a significant positive effect on the performance of employees of the Health Office Maluku Province. The three hypotheses in this study are proven and accepted. Keywords: Organizational culture, work motivation, work discipline and employee performance.